Pengaruh Kualitas Konten terhadap Pendapatan Influencer dengan Engagement rate sebagai Variabel Mediasi - Naily Fithri Karima; Agus Prayitno; Amalia Nur Chasanah; Vicky Oktavia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The rapid growth of social media has fostered the emergence of influencers as a key element in modern digital marketing strategies. Influencer income is no longer determined solely by the number of followers but is also influenced by content quality and audience engagement rate. This study aims to examine the effect of content quality on influencer income with engagement rate as a mediating variable. A quantitative research approach was employed using a survey method. The sample consisted of 120 influencers in Indonesia selected through purposive sampling. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 software. The results indicate that content quality has a positive and significant effect on both engagement rate and influencer income. Furthermore, engagement rate also has a positive and significant effect on influencer income. However, the indirect effect analysis reveals that engagement rate does not mediate the relationship between content quality and influencer income. These findings suggest that content quality has a more dominant direct impact on influencer income rather than through engagement mechanisms. This study provides practical implications for influencers to prioritize content quality improvement as a key strategy for increasing income, and for brands to consider content quality alongside engagement rate when selecting influencers for collaborations.